How Do Turkish Primary School Teachers Reflect Upon Their Priorities Regarding Their Classroom Practices in Meeting Their Gifted Students’ Special Needs? - Savaş Akgül; Ayşin Kaplan Sayı (SAGE Open)
This study aims to determine what factors the primary school teachers working with gifted students prioritize and give importance to in their curriculum designs and explore how these are reflected upon their teaching practices. The research was carried out in the fall semester of the 2020 to 2021 academic year in Türkiye, with the participation of 58 primary school teachers. Data were collected through online semistructured interviews and were analyzed using inductive-oriented content analysis. The findings indicate that the participant teachers are aware of the needs of their gifted and talented students and put some effort into addressing these. However, it is also evidenced that the participant teachers fail to fully provide the support required to improve the students’ skills. Our findings imply that it is crucial to focus particularly on individualized education and differentiated teaching in teacher education and in-service training programs to better address the special needs of students.